2020
DOI: 10.47102/annals-acadmedsg.2020335
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Confidence Level Among Emergency Healthcare Workers in Airway Management and Resuscitation of Suspected COVID-19 Patients: A Cross Sectional Study in Malaysia

Abstract: Introduction: This study aims to evaluate the knowledge and confidence of emergency healthcare workers (EHCW) in facing the COVID-19 pandemic. Materials and Methods: A cross-sectional online study using a validated questionnaire was distributed to doctors (MD), assistant medical officers (AMO), and staff nurses (SN) at an urban tertiary Emergency Department. It comprised of 40 knowledge and 10 confidence-level questions related to resuscitation and airway management steps. Results: A total of 135 from 167 elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 32 publications
2
21
1
Order By: Relevance
“…This study evaluated respondents’ KAP towards the COVID-19 resuscitation protocol by the ERC. Sixty-eight percent (n = 108) respondents had adequate knowledge on COVID-19 resuscitation, similar to previous studies [ [13] , [15] ]. Majority of the respondents had adequate knowledge on COVID-19 mode of transmission, AGP, and proper PPE usage.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study evaluated respondents’ KAP towards the COVID-19 resuscitation protocol by the ERC. Sixty-eight percent (n = 108) respondents had adequate knowledge on COVID-19 resuscitation, similar to previous studies [ [13] , [15] ]. Majority of the respondents had adequate knowledge on COVID-19 mode of transmission, AGP, and proper PPE usage.…”
Section: Discussionsupporting
confidence: 87%
“…Emergency HCW are the first point of contact with COVID-19 patients and are at the highest risk of occupational exposure due to AGP during resuscitation [ [9] , [12] ]. Previous studies have evaluated HCW knowledge on COVID-19 infection control [ [13] , [14] , [15] , [16] ]. Bhagavathula et al found a disparity of knowledge and attitude between doctors and allied heatlh personnel on COVID-19 transmission and disease prevention [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that 68.9% of subjects had a high level of knowledge about airway management and cardiopulmonary resuscitation for COVID‐19 patients. 9 Therefore, it may be possible for Japanese medical students to acquire essential knowledge regarding COVID‐19 context CPR and airway management if adequate learning opportunities are provided. Specifically, two‐person bag‐valve mask ventilation with PPE is an essential airway management skill for senior medical students to learn.…”
Section: Discussionmentioning
confidence: 99%
“…6 This involves augmenting the ICU team with non-intensivists, leaving intensivists to perform supervisory roles. Non-intensivist physicians will then need to be equipped with the necessary skills 8 to function efficiently and safely in a critical care team. The need for mass education and avoidance of face-to-face training during a pandemic makes conventional teaching methods (through the use of task trainers and simulation sessions) logistically difficult.…”
Section: Rapid Training Of Non-intensivists Using An Online Critical Care Course During Covid-19mentioning
confidence: 99%